Both transcriptional regulation and translational control of ATF4 are central to the integrated stress response - Dey, Souvik; Baird, Thomas D; Zhou, Donghui; Palam, Lakshmi Reddy; Spandau, Dan F; Wek, Ronald C (The Journal of biological chemistry, 2010)
In response to different environmental stresses, phosphorylation of eIF2 (eIF2∼P) represses global translation coincident with preferential translation of ATF4. ATF4 is a transcriptional activator of the integrated stress response, a program of gene expression involved in metabolism, nutrient uptake, anti-oxidation, and the activation of additional transcription factors, such as CHOP/GADD153, that can induce apoptosis. Although eIF2-P elicits translational control in response to many different stress arrangements, there are selected stresses, such as exposure to UV irradiation, that do not increase ATF4 expression despite robust eIF2∼P. In this study we addressed the underlying mechanism for variable expression of ATF4 in response to eIF2∼P during different stress conditions and the biological significance of omission of enhanced ATF4 function. We show that in addition to translational control, ATF4 expression is subject to transcriptional regulation. Stress conditions such as endoplasmic reticulum stress induce both transcription and translation of ATF4, which together enhance expression of ATF4 and its target genes in response to eIF2∼P. By contrast, UV irradiation represses ATF4 transcription, which diminishes ATF4 mRNA available for translation during eIF2∼P. eIF2∼P enhances cell survival in response to UV irradiation. However, forced expression of ATF4 and its target gene CHOP leads to increased sensitivity to UV irradiation. This combination of transcriptional regulation and translational control allows the eIF2 kinase pathway to selectively repress or activate key regulatory genes subject to preferential translation, providing the integrated stress response versatility to direct the transcriptome that is essential for maintaining the balance between stress remediation and apoptosis.